Assessment of the language proficiency and its correlation to classroom language: a case study on primary school English teacher (Conference on English Language Teaching, 2023)
The rapid development of the educational system in Indonesia is reflected in thegrowth of educational institutions. Relevant studies shown for the last ten years,parental decision in Indonesia tends to prefer private schools for their children topublic ones with a rationale that teachers in private schools offer more quality. Thisstudy aims to investigate the language proficiency of the teachers in One Earth School,Denpasar Bali, based on the CEFR assessment framework and its relation to theability of teachers in performing classroom language. This study employs a case studydesign with three teachers as the subjects. The teachers selected are those who fulfillthe criteria to be subjects seen from its experience and actively engaged inprofessional development. The data are collected by utilizing several means such asspeaking test proficiency with CEFR based assessment, document study, and fieldobservation. This study is expected to give a contribution on empowering Englishteachers to engage in professional development and displaying a clear picturewhether or not teachers with certain proficiency levels could successfully transformthem in classroom language.